Best practices in nutrition science to earn and keep the public's trust. Issue 1 (18th January 2019) - Garza, Cutberto; Stover, Patrick J; Ohlhorst, Sarah D; Field, Martha S; Steinbrook, Robert; Rowe, Sylvia; Woteki, Catherine; Campbell, Eric
ABSTRACT: Public trust in nutrition science is the foundation on which nutrition and health progress is based, including sound public health. An ASN-commissioned, independent Advisory Committee comprehensively reviewed the literature and available public surveys about the public's trust in nutrition science and the factors that influence it and conducted stakeholder outreach regarding publicly available information. The Committee selected 7 overlapping domains projected to significantly influence public trust: 1 ) conflict of interest and objectivity; 2 ) public benefit; 3 ) standards of scientific rigor and reproducibility; 4 ) transparency; 5 ) equity; 6 ) information dissemination (education, communication, and marketing); and 7 ) accountability. The literature review comprehensively explored current practices and threats to public trust in nutrition science, including gaps that erode trust. Unfortunately, there is a paucity of peer-reviewed material specifically focused on nutrition science. Available material was examined, and its analysis informed the development of priority best practices. The Committee proposed best practices to support public trust, appropriate to ASN and other food and nutrition organizations motivated by the conviction that public trust remains key to the realization of the benefits of past, present, and future scientific advances. The adoption of the best practices by food and nutrition organizations, such as ASN, other stakeholder organizations, researchers, food and nutrition professionals, companies, government officials, and individuals working in the food and nutrition space would strengthen and help ensure earning and keeping the public's continued trust in nutrition science.